2001
DOI: 10.1046/j.1440-1673.2001.00926.x
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the transverse cerebellar diameter in preterm neonates and its use in assessment of gestational age

Abstract: The transverse cerebellar diameter (TCD) serves as a reliable predictor of gestational age (GA) in the fetus and is a standard against which aberrations in other fetal parameters can be compared, especially when the GA cannot be determined by the date of the last menstrual period or an early pregnancy scan. [1][2][3] There are preliminary data available for preterm neonates from 23 to 32 weeks and 6 days (32 +6 ) GA. 4 These data correlate TCD with GA assessed to completed whole weeks of gestation, and the TCD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 19 publications
2
24
0
2
Order By: Relevance
“…Similar to our findings, fetal imaging studies have shown that TCD correlates closely with GA and that the increase in TCD is linear during the second [20][21][22] and third trimester [5,14,19]. Also, it has been shown that this correlation is not affected significantly by sex, fetal growth restriction, multiple pregnancy, or fetal macrosomy [9,21,23,24].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similar to our findings, fetal imaging studies have shown that TCD correlates closely with GA and that the increase in TCD is linear during the second [20][21][22] and third trimester [5,14,19]. Also, it has been shown that this correlation is not affected significantly by sex, fetal growth restriction, multiple pregnancy, or fetal macrosomy [9,21,23,24].…”
Section: Discussionsupporting
confidence: 90%
“…The study by Davies et al [14] aimed to confirm the relationship between GA and TCD to define the prediction of GA by TCD and assess the reliability of TCD measurements. TCD was measured in a total of 221 infants with known GA. TCD correlates closely with GA and predicts GA to ± 2.33 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…6 TCD has emerged as a useful parameter for assessing fetal growth retardation. 7 The purpose of the current study is to evaluate the accuracy of transverse cerebellar diameter as against the conventional parameters in assessing gestational age in normal pregnant mothers between 15 to 40 weeks and its usefulness in antenatal diagnosis of intrauterine growth retardation.…”
Section: Introductionmentioning
confidence: 99%
“…62 Another study confirmed the relationship between gestational age and transverse cerebellar diameter. 63 Doppler ultrasound parameters can serve as a tool for predicting developmental delay. It was found that the leftward hemodynamic status of the middle cerebral arteries, as measured by cranial Doppler ultrasound in the neonatal period, predicts early motor outcome in term infants.…”
mentioning
confidence: 99%